Believe it or not, it's all about beliefs! - Fabrice Collard; Patrick Fève; Alain Guay (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2024)
This paper studies the impact of Higher Order Belief (HOB) shocks, representing shifts in agents' beliefs about others' beliefs, on macroeconomic outcomes. The dynamic causal effects of these shocks are identified by leveraging a combination of a proxy-VAR approach and DSGE-based instruments. Our findings suggest that HOB shocks are indeed a key driver of the business cycle and account for a sizeable share of the observed business cycle volatility. Finally, our identification approach ensures that these shocks are not confounded with other structural/fundamental shocks.
Keywords: C32; E32; 330; Higher Order Beliefs; Business cycles; proxy-VAR; DSGE